Oviposition preference hierarchy in Ceratitis capitata (Diptera, Tephritidae): influence of female age and experience - Joachim-Bravo, Iara S.; Fernandes, Odair A. [UNESP]; Bortoli, Sérgio A. [UNESP]; Zucoloto, Fernando S. (Fundação Zoobotânica do Rio Grande do Sul, 2001)
The influence of two factors, age and previous experience, on the oviposition hierarchy preference of Ceratitis capitata (Wiedemann, 1824) females was studied. Two populations were analyzed: one reared in laboratory during 17 years and the other captured in nature. In the first experiment the oviposition preference for four fruits, papaya, orange, banana and apple was tested at the beginning of oviposition period and 20 days past. The results showed that the wild females as much the laboratory ones had an oviposition preference hierarchy at the beginning of peak period of oviposition. However this hierarchic preference disappeared in a later phase of life. In the second experiment the females were previously exposed to fruits of different hierarchic positions and afterwards their choice was tested in respect to the oviposition preference for those fruits. The results showed that there was an influence of the previous experience on the posterior choice of fruits to oviposition when the females were exposed to fruits of lower hierarchic position.
Keywords: Medfly; hosts; Behavior; oviposition; Ceratitis